The effect of labour on the coagulation system in the term neonate. (8th April 2013) - Kulkarni, A. A.; Osmond, M.; Bapir, M.; Riddell, A.; Smith, C.; Lee, C. A.; Kadir, R. A.
Summary The coagulation system of the foetus is markedly different from that of adults. To assess the influence of maternal age, mode of delivery and intrapartum events, and foetal gender and weight on the foetal coagulation system. Cord blood was collected from 154 healthy pregnant women, with gestational age 37 – 42 weeks at birth. Mann–Whitney test was used for analysis of binary data and continuous variables were analysed using Pearson's correlation coefficient. Mean cord blood levels of FVIII:C, VWF:Ag, VWF:CB, FIX, FXI, FXII and plasminogen were significantly higher in babies delivered after labour, compared to those delivered after an elective caesarean. Mean cord blood levels of FII (P = 0.003), FV (P = 0.009), FVII (P = 0.0004) and FX (P = 0.0009) were significantly lower in the babies with meconium stained liquor in labour, compared with those with clear liquor. Augmentation with oxytocin, instrumental delivery, did not affect any of the factor levels and duration of labour did not have an effect on the level of coagulation proteins in cord blood. This study provides valuable information about effect of labour on the coagulation system of the foetus. It is concluded that, in cord blood, the results of coagulation parameters in the newborn baby should be considered in light of mode of delivery and events of labour.